The present-day atmospheric dust deposition process in the South China Sea. (15th February 2020) - Du, Shuhuan; Xiang, Rong; Liu, Jianguo; Liu, J. Paul; Islam, G.M. Ariful; Chen, Muhong
Abstract: Modern dust plays essential roles in marine and climate processes, which bring continental material to the ocean and sensitivity in marine ecosystems. However, the atmospheric dust deposition process has rarely been studied in the South China Sea (SCS). Here, we present 51 atmospheric dust samples, collected along the SCS, to investigate the grain size distribution, depositional flux, and features revealed by scanning electron microscopy, combined with 5-day back trajectories to indicate the present-day dust deposition process for the first time. The grain size distribution and depositional flux of aerosol samples illustrate the seasonal trend: coarser particle and higher flux mass in winter than summer. The average grain size is 5.75 μm during winter and 3.62 μm from summer, and the depositional flux in the winter is 1.4 times than that in summer, both are related to the transport pathway and power of the East Asian monsoon. Modeled 5-day back trajectories of dust samples suggest a southwesterly transport pathway in summer and the Southeast Asian monsoon as a possible source of the dust loading, while the northeast winds drove the aeolian dust transport during the winter monsoon from the Asian continent. Meanwhile, westerly circulation conveys the fine particles (~0.63 μm) as the stable terrigenous component into the SCS, deposited through the entire dust deposition process from the atmosphere and water to the surface sediment. Furthermore, the surface of quartz particles from atmospheric dust shows the unique structure in the aeolian environment as a reference to distinguish the different continental components in the sediments. This study provides new insights into the present-day dust deposition process in the SCS, significantly extending the current understanding of the relationship between atmospheric dust and the marginal sea. Highlights: Present-day dust grain size, seasonal trend change due to wind strength and dust availability in the South China Sea. Modeled 5-day back trajectories show transport pathway and source in different prevailing monsoon for dust deposition. Scanning electron microscope as a reference to distinguish continent components from terrigenous sediments.